Seeking the truth in Turkish literature and Besir Fuat - Gülşen, Hacer (Selçuk Univ, Inst Turkish Studies, Marasal Fevzi Cakmak Mah, Konya, Selcuklu 00000, Turkey, 2017)
Literature is the science of beauty that blossoms into the inner human world. There are those who say truth cannot be sought in this science, as well as those who pursue the absolute truth. Should truth be sought in literature today as in the past? Or shouldn't it? The question seems to be an unresolved problem. In fact, it is known that every literary work has a fictional side to it. Consequently, more than a few artists believe that truth in literary works is an adorned truth. The concept of truth in Turkish literature that developed especially during what we call the Tanzimat (reformation) period (in Ottoman history) under western influence comprises a remarkable feature. Because people change and literature that has it as a subject needs to keep pace with this change. The currents of truth, realism and, a step further, naturalism, which artists including Sinasi, Namik Kemal and Ahmet Midhat particularly dwell upon, begin to keep the agenda busy. In the period we call the intermediate generation, we come across Besir Fuat and artists who followed his footsteps. The method used in this article is one of criticism directed to the artist. To understand the artist one needs to look at his work and evaluate him accordingly. This principle carries importance in the method in question.
Keywords: Literature; Turkish Literature; Truth; Besir Fuat